2005
DOI: 10.1073/pnas.0503890102
|View full text |Cite
|
Sign up to set email alerts
|

Physics and evolution of thermophilic adaptation

Abstract: Analysis of structures and sequences of several hyperthermostable proteins from various sources reveals two major physical mechanisms of their thermostabilization. The first mechanism is ''structure-based,'' whereby some hyperthermostable proteins are significantly more compact than their mesophilic homologues, while no particular interaction type appears to cause stabilization; rather, a sheer number of interactions is responsible for thermostability. Other hyperthermostable proteins employ an alternative, ''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
217
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(233 citation statements)
references
References 30 publications
15
217
1
Order By: Relevance
“…Our result is in agreement with the previous findings to define the minimal pharmacophore in moenomycin, in which the EF-ring phosphoglycerate portion together with either the C or the D ring forms critical interactions with proteins (8). Although A. aeolicus (11), like E. coli, was classified as Gram-negative bacterium, the interaction pattern with moenomycin in AaPGT showed differences from our structure and SaPBP2 ( Fig. 2 B and C).…”
Section: Resultssupporting
confidence: 82%
“…Our result is in agreement with the previous findings to define the minimal pharmacophore in moenomycin, in which the EF-ring phosphoglycerate portion together with either the C or the D ring forms critical interactions with proteins (8). Although A. aeolicus (11), like E. coli, was classified as Gram-negative bacterium, the interaction pattern with moenomycin in AaPGT showed differences from our structure and SaPBP2 ( Fig. 2 B and C).…”
Section: Resultssupporting
confidence: 82%
“…at the earliest (prebiotic) stages of evolution. It seems therefore likely that emergence of wonderfolds dominated the physical selection and design of first thermostable proteins in the course of prebiotic evolution (36).…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12] Although most hydrogen-bonded sidechain interactions that have been experimentally measured in membrane proteins appear to make relatively modest contributions, [21][22][23][24][25][26][27] some have been measured as high as 1.8 kcal/mol and in theory it is possible that they could be made even stronger. 26,28 Thus, it seems reasonable to expect that the number of transmembrane interhelical hydrogen bonds might increase in thermophiles.…”
Section: Interhelical Hydrogen Bonding In Thermophiles and Mesophilesmentioning
confidence: 99%
“…As a result, the stabilizing mechanisms have been extensively explored for water-soluble proteins. The mechanisms observed include an increase in secondary structure propensity; 1,2 changes that decrease unfolded state entropy such as the introduction of Pro residues, reduction of Gly residues, 3 smaller loops, 4 and the addition of disulfide bonds; [5][6][7] an increase of hydrogen bonds and salt bridges; [8][9][10][11][12] and better optimized hydrophobicity. 13 Szilagyi and Zavodszky 3 made an extensive study of many protein families and found that few of these mechanisms were general, except an increase in salt bridges.…”
Section: Introductionmentioning
confidence: 99%